Evaluation on Monocyte-Mediated Delivery of a Therapeutic Gene into the Inflamed Brain - Tong, Hsin-I; Kang, Wen; Zhou, Guangzhou; Liu, Min; Shi, Yingli; Lu, Yuanan (Current Gene Therapy, 2016)
Objective: This study was aimed to explore the potential of a non-invasive monocytes-based delivery system to transport therapeutic genes into the diseased brain. The study was conducted by first establishing the optimized conditions for lentiviral vector (LV)-mediated gene transfer into freshly isolated monocytes, followed by investigating the inflamed-brain homing efficiency and in vivo cell-mediated transgene expression by carrier monocytes in a mouse model with acute sub-regional neuroinflammation. Materials & Methods: Using a newly optimized spin-infection method, up to 35% of freshly isolated monocytes were successfully transduced with the LV system DHIV-101 at M.O.I. of 10. Meanwhile, cell trafficking and accumulation were detected in the inflamed brain regions in high density following intravenous (IV) administration of freshly isolated monocytes, confirming the suitability of using monocytes as cellular vehicles targeting the brain. However, LV transduced monocytes (TD-MO) displayed significantly reduced homing efficiency into the brain, possibly due to the initial unhealthy cellular states following LV transduction. Although the presence of transgene in the brain was confirmed by PCR, transgene expression was not detected within the inflammatory central nervous system (CNS) sites by RT-PCR or ELISA. Instead, high density of functional TD-MO and their transgene products were detected in the spleen. Conclusion: In conclusion, this study demonstrated that IV-infused monocytes were able to migrate into the brain, and remain viable and functional in vivo following LV transduction, warranting more indepth research to fully establish the conditions in order to reduce cellular toxicity induced by vector transduction, and thus enhance the brain homing efficiency of carrier monocytes.
Keywords: Gene therapy